Characterizing a thermostable Cas9 for bacterial genome editing and silencing - Ioannis Mougiakos; Prarthana Mohanraju; Elleke F. Bosma; Valentijn Vrouwe; Max Finger Bou; Mihris I. S. Naduthodi; Alex Gussak; Rudolf B. L. Brinkman; Richard van Kranenburg; John van der Oost (Nature Communications, 2017)
CRISPR-Cas9 genome engineering tools have found wide application in a range of species, however they are unsuitable for applications at elevated temperatures. Here the authors characterise ThermoCas9 from which is functional from 20°C to 70°C.